2006
DOI: 10.2307/20111852
|View full text |Cite
|
Sign up to set email alerts
|

Male White-Black Wage Gaps, 1979-1994: A Distributional Analysis

Abstract: for their helpful comments and suggestions. I also thank Jared Bernstein for sharing his copy of the February 1990 CPS file, and thank seminar participants of the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
5
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Reardon (1997) shows that the general inequality story of skill biased technical change may be particularly important in explaining racial inequality growth among highly skilled blacks and whites. Similarly, Rogers (2006) shows that the stretching (increased variance of wages) of the skill distribution during the 1980s explains the growth in within group white-black wage gaps at the top of that distribution. Related work by Bound and Freeman (1992) and by Chay and Lee (2000) document a widening in the black white earnings differential for young men over the 1980s and 2 Although Johnson and Neal (1998) are quick to emphasize that only five percent of black men in their sample score more than one standard deviation above the mean.…”
Section: Further Motivationmentioning
confidence: 95%
“…Reardon (1997) shows that the general inequality story of skill biased technical change may be particularly important in explaining racial inequality growth among highly skilled blacks and whites. Similarly, Rogers (2006) shows that the stretching (increased variance of wages) of the skill distribution during the 1980s explains the growth in within group white-black wage gaps at the top of that distribution. Related work by Bound and Freeman (1992) and by Chay and Lee (2000) document a widening in the black white earnings differential for young men over the 1980s and 2 Although Johnson and Neal (1998) are quick to emphasize that only five percent of black men in their sample score more than one standard deviation above the mean.…”
Section: Further Motivationmentioning
confidence: 95%
“…Braddock and McPartland, 1987;Bound and Freeman, 1992;Fugazza, 2003;Kaufman, 1983). However, the fact remains that Black men are still paid less than White men overall (Bound and Freeman, 1992;Chandra, 2000;Fugazza, 2003;Rodgers, 2006). The current paper will take a new perspective on the issue of wage gaps between Black and White employees.…”
mentioning
confidence: 95%
“…However, the closing of the wage differential ceased during the mid-1970s, and it is not clear why the wage stagnation occurred (Smith, 1993). In fact, there is evidence that the gap widened again in the 1980s (Rodgers, 2006), and is still present today. Chandra (2000) found that in 1990, Black men made about 76 percent of White men's dollar, and census data from 2000 found that the median overall income for White households was $46,305 while the median overall income for Black households was only $29,470, which is only 64 percent of the White household income (US Census Bureau, 2000).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“… By using the 1979–1994 Current Population Survey Outgoing Rotation Group files, Rodgers (2006) finds that the black‐white male wage gap expanded as new entrants turned into prime‐age workers. He points out that the growing male racial wage gap as these men aged could be a result of racial differences in regenerative human capital investment. …”
mentioning
confidence: 99%